From Basic to Clinical Immunology: manual - Климов, В. В. аллергология и иммунология 19540502 Владимир Васильевич (Springer, 2019)
This book fills a gap at the interface of fundamental and clinical immunology, and allergy. For many years, experts in fundamental immunology and physicians involved in clinical immunology and allergy worked separately - but the fundamental immunologists did not have medical qualifications and the physicians were not involved in the field of fundamental research. Written by a teacher and an expert in both fields, this book combines current knowledge on basic immunology and immunopathology with clinical comments that complete the whole picture.Immunology is a complex science, which requires a simplified approach in order to be taught and understood effectively. This book is based on the authors' long experience in teaching undergraduate, postgraduate students and interns both basic and clinical immunology. Reviewing a variety of important components related to the immune system, it is clearly and logically structured, and enriched by figures, tables and boxes with important immunology definitions. Each chapter has its own bibliography, and most units include links to electronic quizzes and audio files to accompany readers step by step. This easy-to-follow volume concludes with suggestions for future study. It is a valuable resource for undergraduate and postgraduate students, as well as medical practitioners.